[2,3,7,8,13,14,17,18-Octakis(ethylsulfanyl)-5,10,15,20-porphyrazinato]zinc(II) - Akkurt, Mehmet; Coskun, Naciye Yilmaz; Kilicaslan, Fatma Aytan; Yalcin, Sabiha Manav; Buyukgungor, Orhan; Gul, Ahmet (INT UNION CRYSTALLOGRAPHY, 2010)
In the title compound, [Zn(C32H40N8S8)], the ZnII ion is coordinated by four N atoms in a slightly distorted square-planar environment. In addition, there is a Zn...S contact involving a symmetry-related S atom which, when considered, forms a pseudo-square-pyramidal coordination with respect to the ZnII ion. Three of the ethyl groups are disordered over two sites with occupancy ratios of 0.841 (10):0.159 (10), 0.802 (10):0.198 (10) and 0.457 (13):0.543 (13). Weak intramolecular C-H...N and C-H...S interactions contribute to the stability of the molecular conformation. Intermolecular C-H...S contacts, weak C-H...pi interactions and pi-pi stacking interactions [centroid-centriod distances = 3.832 (4) and 3.850 (5) A] contribute to the stabilization of the crystal structure.
Keywords: Crystallography